1982
DOI: 10.1071/ea9820209
|View full text |Cite
|
Sign up to set email alerts
|

Population estimates of cereal cyst nematode and response of wheat to granular nematicides

Abstract: Response of vegetative growth and grain yield of wheat Triticum aestivum cv. Condor to the control of cereal cyst nematode Heterodera avenae by nematicides applied with the seed, in the drill row was assessed in twenty field trials. These trials were conducted in 1978 on three soil types near Coonalpyn, South Australia. Aldicarb was used at all sites and fosthietan and terbufos at four sites. Significant grain yield increases to aldicarb were obtained at 12 sites while yields were increased by the three nemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The sown pastures were not legume dominant, being only of little better quality than the volunteer pastures (KING 1984). As a result they provided little extra soil nitrogen, disease control or growth of following crops.…”
Section: Nitrogenmentioning
confidence: 99%
See 3 more Smart Citations
“…The sown pastures were not legume dominant, being only of little better quality than the volunteer pastures (KING 1984). As a result they provided little extra soil nitrogen, disease control or growth of following crops.…”
Section: Nitrogenmentioning
confidence: 99%
“…tritici and R. solani (following grassy pasture in the rotation) and from low disease treatments in the crop rotation experiment reported by KING (1984). The mean wheat and barley yields A complete description of the treatments and general management of the crop rotation experiment may be found in KING (1984). Briefly, the experiment was undertaken from 1976 to 1979 and was located near Coonalpyn in the Upper South East of South Australia on a red duplex soil (Dr. 2.23, Northcote 1971).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Apart from the seed dressings already mentioned, these are seed furrow treatments of EDB 3.7 1 ha-1 , terbufos 4 kg ha-1 , aldicarb 2 kg ha-1 or carbofuran 1.1 1 ha-1 • Increases of 30% or more in wheat yields following these treatments are common (Brown, 1984a). However, King et al (1982) showed that grain yield increases due to aldicarb which were statistically significant in 12 of 20 field experiments, could not be correlated with nematode egg density in the soil, length of seminal root axes, or severity of 'knotting' of the roots due to nematode attack. An ultra-low-volume applicator was developed for the application of small volumes of liquid nematicides in the seed furrows during sowing (Gurner et al, 1980), Using this equipment, small volumes of EDB or dichloropropene similarly applied did not improve the yield of susceptible oats in sandy loam infested with H. avenae in England, probably because of phytotoxicity, whereas 1.5 kg oxamyl ha-1 in the seed furrows greatly increased oat grain yield (Whitehead et al, 1982).…”
Section: Seed Furrow and Row Treatmentsmentioning
confidence: 99%